Rotavirus VP6 as an Adjuvant for Bivalent Norovirus Vaccine Produced in Nicotiana benthamiana - Maria Malm; André Diessner; Kirsi Tamminen; Markus Liebscher; Timo Vesikari; Vesna Blazevic (MDPI AG, 2019)
Rotaviruses (RVs) and noroviruses (NoVs) are major causes of childhood acute gastroenteritis. During development of a combination vaccine based on NoV virus-like particles (VLP) and RV VP6 produced in baculovirus expression system in insect cells, a dual role of VP6 as a vaccine antigen and an adjuvant for NoV-specific immune responses was discovered. Here the VP6 adjuvant effect on bivalent GI.4 and GII.4-2006a NoV VLPs produced in Nicotiana benthamiana was investigated. BALB/c mice were immunized intradermally with suboptimal (0.3 µg) dose of each NoV VLP alone or combined with 10 µg of VP6, or equal doses of NoV VLPs and VP6 (1 µg/antigen). NoV-specific serum IgG antibodies and their blocking activity were analyzed using vaccine-homologous and heterologous NoV VLPs. Immunization with 0.3 µg NoV VLPs alone was insufficient to induce NoV-specific immune responses, but with co-administration of 10 µg of VP6, antibodies against vaccine-derived and heterologous NoV genotypes were generated. Furthermore, corresponding adjuvant effect of VP6 was observed with 1 µg dose. Efficient uptake and presentation of VP6 by dendritic cells was demonstrated in vitro. These results show that adjuvant effect of VP6 on bivalent NoV VLP vaccine is independent of the cell source used for vaccine production.